Equivalence and Research Design Optimization for International Market Segmentation - Carter, Larry L. (Journal of Marketing Development and Competitiveness, 2019)
The massive growth of global competition has led firms to attempt various international market segmentation schemas; however, creating effective cross-border strategies is often fraught with unique challenges. The purpose of this study is to address the issues concerning equivalence and to propose a two-stage approach towards effective international market segmentation. The study consolidates equivalence issues specific to international research that may increase the likelihood of bias into the segmentation process. An exhaustive set of propositions is attempted to help firms improve their international market segmentation efforts and bolster their competitiveness in this global marketplace.